2020
DOI: 10.1111/str.12349
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of large, discontinuous displacement from digital images

Abstract: One main limitation of conventional digital image correlation (DIC) methods is their incapacity to treat with large, discontinuous displacements. This paper seeks to resolve this issue using a variational method. Specifically, the objective function is written in a form of L1‐norm instead of L2‐norm for discontinuity preservation. This convex, non‐differentiable objective function is resolved by a proximal gradient method. Then, the entire correlation process is embedded into a multi‐level image pyramid, enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Discontinuity issues in the DIC calculation have challenged the analysis of rock failure processes. Discontinuous significant displacement problems can be addressed through algorithm modifications, enabling the quantification of crack propagation . Additionally, experimental results have shown that the roughness of fracture surfaces exhibits certain characteristic scaling properties. , It provides insights into using the DIC method to extract fracture surface morphology and calculate fracture roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Discontinuity issues in the DIC calculation have challenged the analysis of rock failure processes. Discontinuous significant displacement problems can be addressed through algorithm modifications, enabling the quantification of crack propagation . Additionally, experimental results have shown that the roughness of fracture surfaces exhibits certain characteristic scaling properties. , It provides insights into using the DIC method to extract fracture surface morphology and calculate fracture roughness.…”
Section: Introductionmentioning
confidence: 99%